Dispersion of finite-size, non-spherical particles by waves and currents. (10th January 2023) - Clark, Laura K.; DiBenedetto, Michelle H.; Ouellette, Nicholas T.; Koseff, Jeffrey R.
Abstract: Abstract : We present the results of a set of experiments designed to measure the dispersion of non-spherical particles in a wave–current flow. We released negatively buoyant discs, rods and unit-aspect-ratio cylinders into a flow both with and without waves and analysed their respective landing positions to quantify how much they had dispersed while in the flow. We found that the presence of waves significantly increased the dispersion of the particles, and that the magnitude of this increase depends on particle shape and volume. In particular, thinner rods and thinner discs have greater relative dispersion than thicker rods and thicker discs, respectively, and smaller particles have greater relative dispersion than larger particles. Although the particles travelled farther in the presence of waves, the increase in dispersion was much greater than could be explained solely by increased transport distance. These results indicate that models of microplastic transport must account for waves as well as particle characteristics.